2009
DOI: 10.1158/1055-9965.epi-08-0745
|View full text |Cite
|
Sign up to set email alerts
|

Five Polymorphisms and Breast Cancer Risk: Results from the Breast Cancer Association Consortium

Abstract: Previous studies have suggested that minor alleles for ERCC4 rs744154, TNF rs361525, CASP10 rs13010627, PGR rs1042838, and BID rs8190315 may influence breast cancer risk, but the evidence is inconclusive due to their small sample size. These polymorphisms were genotyped in more than 30,000 breast cancer cases and 30,000 controls, primarily of European descent, from 30 studies in the Breast Cancer Association Consortium. We calculated odds ratios (OR) and 95% confidence intervals (95% CI) as a measure of associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 18 publications
(12 reference statements)
5
34
0
Order By: Relevance
“…Several sensitivity analyses were performed (see Materials and Methods) but results did not change substantially and so those from the main analysis are presented in this report. Subsequent to the initiation of this study, a study from the Breast Cancer Association Consortium (BCAC), performed in 430 000 breast cancer cases and 30 000 controls has now found no evidence for an association of rs744154 with breast cancer risk in the general population (Gaudet et al, 2009). This is consistent with the lack of association found for BRCA1 and BRCA2 mutation carriers.…”
Section: Resultssupporting
confidence: 59%
“…Several sensitivity analyses were performed (see Materials and Methods) but results did not change substantially and so those from the main analysis are presented in this report. Subsequent to the initiation of this study, a study from the Breast Cancer Association Consortium (BCAC), performed in 430 000 breast cancer cases and 30 000 controls has now found no evidence for an association of rs744154 with breast cancer risk in the general population (Gaudet et al, 2009). This is consistent with the lack of association found for BRCA1 and BRCA2 mutation carriers.…”
Section: Resultssupporting
confidence: 59%
“…For TNF-a-238G>A, 3 studies, comprising 4 data sets with 35,578 cases and 38,095 controls, were identified for analyzing its connection with breast cancer susceptibility. Similarly, the cohort data from Gaudet et al [6] can be divided into 2 subsets based on ethnicity, which will be evaluated further (tables 1 and 2).…”
Section: Literature Characteristicsmentioning
confidence: 99%
“…Our results suggested that the influence of the individual data sets on OR estimation was significant. The cohort data from Gaudet et al [6] is the most influential ( fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2008) and Frank et al (2006) evaluated CASP10 rs13006529 polymorphism on the risk of cutaneous melanoma and familial breast cancer, with neither of the results reaching statistical significance. In the breast cancer, rs13010627 of CASP10 was found to be associated with a decreased risk (OR AA+AG : 0.62, 95% CI: 0.43-0.88) (Frank et al, 2006); however, this conclusion failed to remain significant in a subsequent large-scale pooled analysis (OR AA : 0.94, 95% CI: 0.72-1.22; OR AG : 1.03, 95% CI: 0.98-1.09) (Gaudet et al, 2009). Oh et al (2010) showed that CASP10 polymorphism increased the risk of CRC.…”
Section: Discussionmentioning
confidence: 91%